Tren Akad Pembiayaan di BPRS Indonesia: Dominasi Murabahah dan Kebangkitan Musyarakah dalam Perspektif 2015–2024 - Siyamto, Yudi; Murdapa, Purnama Andri; Maelana, Herman Wahyu Dwi (Nur Science Institute, 2025)
This study aims to analyze the trends in the use of financing contracts at Islamic Rural Banks (BPRS) in Indonesia during the 2015 to 2024 period. The research employs a descriptive quantitative method utilizing secondary data sourced from financial reports and official statistics published by the Financial Services Authority (OJK), KNEKS, and other related sources. The results reveal that Murabahah remains the dominant contract throughout the study period, despite a significant decrease from 77.91% in 2015 to 55.95% in 2024. In contrast, the proportion of Musyarakah contracts increased markedly from 11.31% in 2015 to 26.47% in 2024, indicating growing diversification into profit-and-loss sharing financing products. These findings signify a positive shift toward the implementation of justice and profit and loss sharing principles in Islamic microfinance. This study is expected to serve as a reference for the development of more equitable and sustainable micro-shariah financing policies in the future.